Old Testament Anthropology in the Translation of the Septuagint: the Composition of the Human Being (Fundamental Principles) - . VEVYURKO (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2015)
The author examines the meaning of the Old Testament corpus contained in the Greek translation of the Septuagint in order to better understand the anthropology of the Bible on the basis of the work of classiﬁ cation done by G. Wolﬀ in his survey. The author studies the derivation of terminology and deﬁnes its original meaning. This is fundamental for the study of the way the human person was conceived on the cusp of the Old and New Testaments. The Septuagint translation may be analyzed under two aspects: etymology and interpretation. In many cases, the translation allows us to understand more clearly how the translators understood not only individual words but also whole concepts. The author understands the term biblical anthropology in the German sense as the description of the nature of the human person and his place in the world from the point of view of the Bible. The author highlights the semantics underlying the use of the term body (soma), which in itself is poorly conveyed by ancient Hebrew, but which is used in the Septuagint in a way consistent with that employed by the New Testament. The word body describes the ﬁgure of the human person with great objectivity and is itself replete with deﬁnite descriptive attributes. Also new is the understanding of the word spirit (pneuma), which, in this case, is used to describe a person. In this context, it begins to enter the anthropological lexicon and at the same time foreshadows its use in the problematic surrounding early-Christian trichotomy.